EML1–ABL1 Is Activated by Coiled-Coil-Mediated Oligomerization and Induces T-Cell Acute Lymphoblastic Leukemia or Myeloproliferative Disease in a Mouse Bone Marrow Transplant Model. Issue 2 (March 2018) - Vanden Bempt, Marlies; Mentens, Nicole; Vandenberghe, Peter; Cools, Jan; De Keersmaecker, Kim
Abstract : Supplemental Digital Content is available in the text